Brown spot of rice in West Africa: identification of causal species and genetic diversity of Bipolaris oryzae et Exserohilum rostratum - (:unkn) unknown (My University, 2022)
Rice is the second most produced cereal in the world. In Africa, many countries are pinning their hopes on local rice production to achieve food security. But phytosanitary problems contribute to food insecurity. Brown spot of rice is a fungal disease that can attack rice at any stage of its development. In sub-Saharan Africa, this disease is on the rise in many countries and causes losses of about 3.3% of production. Despite this situation, the species responsible for the disease, the genetic diversity and the structure of their populations remain poorly known. This knowledge is essential for the development of effective strategies for the control of Brown spot ofrice in West Africa. The objectives of this thesis were: (i) to identify the species responsible for Brown spot of rice in West Africa and to evaluate their pathogenesis in acontrolled environment, (ii) to analyze the genetic diversity and the mode of reproduction of the most frequent species, (iii) and to develop detection tools. Characterization by genotyping-by-sequencing (GBS) of 469 isolates isolated from the symptoms of Brown spot of rice allowed to assign the isolates to species: two major species, Bipolaris oryzae (37%) and Exserohilum rostatum (41%), and 9 less frequent species (<5%; B. bicolor, B. maydis, B. sorokiniana, B. secalis, B. yamadae, Curvularia hawaiiensis, C.papendorfii, C. spicifera and E. turcicum). The two most frequent species were identified in most of the countries sampled. The analysis of the genetic structure of B. oryzae and E. rostratum carried out on samples from 6 ricegrowing areas of Burkina Faso showed that genetic differentiation was greater within populations than between populations. Each of the species was structured into 4 genetic groups whose distribution was independent of the geographic origin of the isolates. Evidence of recombination has been identified in populations of B. oryzae and E. rostratum. The relative frequencies of mat
Keywords: African Research